The Use of WhatsApp as a Learning Media in Class 5 Madrasah Ibtidaiyah During the Covid-19 Pandemic: Penggunaan WhatsApp sebagai Media Pembelajaran di Kelas 5 Madrasah Ibtidaiyah Selama Masa Pandemi Covid-19 - Dwiki Sayoga Putra; Moch Bahak Udin By Arifin (Universitas Muhammadiyah Sidoarjo, 2022)
This qualitative study examines the utilization of WhatsApp as a learning medium during the Covid-19 pandemic in a primary school setting. The research focuses on grade 5 students at MI Nurul Huda Ngampelsari Sidoarjo, aiming to (1) describe the use of WhatsApp as a learning medium, (2) identify the obstacles encountered, and (3) propose solutions to overcome these challenges. Data were collected through observation, interviews, and documentation. The findings shed light on the potential of WhatsApp for remote learning, highlighting its effectiveness in facilitating communication and content dissemination. However, various obstacles, such as connectivity issues and limited interactivity, were identified. The study suggests solutions, including optimizing infrastructure, promoting student engagement, and integrating complementary platforms. The implications of this research contribute to enhancing the understanding and implementation of digital learning tools during crisis situations, benefiting educational stakeholders worldwide. Highlights: The use of WhatsApp as a learning medium during the Covid-19 pandemic: This study explores the effectiveness and potential of WhatsApp in facilitating remote learning for grade 5 students amidst the Covid-19 crisis. Obstacles in using WhatsApp as a learning medium during the Covid-19 pandemic: The research identifies and discusses the challenges faced in implementing WhatsApp as an educational tool, including issues related to connectivity and limited interactivity. Solutions to overcome obstacles in using WhatsApp as a learning medium during the Covid-19 pandemic: The study proposes practical solutions to address the identified challenges, such as optimizing infrastructure, promoting student engagement, and integrating complementary platforms to enhance the effectiveness of WhatsApp as a remote learning tool. Keywords: WhatsApp, learning medium, Covid-19 pandemic, grade 5 students, qualitative research.